Revision of the species of the New World genus Augochlora (Hymenoptera, Halictidae) occurring in the southern temperate areas of its range - Dalmazzo, Maria de Los Milagros (2011)
Augochlora is a genus of mainly tropical bees, with few representatives in both North and South American temperateareas. In this contribution we present a taxonomic review of the species with southernmost distribution. Only five speciesoccur in central Argentina and Uruguay, between 30º and 40º south latitude: A. iphigenia Holmberg, A. amphitrite(Schrottky), A. nausicaa (Schrottky), A. phoemonoe (Schrottky) and A. daphnis Smith. The first four species are commonelements in the bee assemblages of the area. The fifth species, from Montevideo, Uruguay, is known from the typespecimen only. Re-descriptions of all species, as well as illustrations, distributional data, and taxonomic keys arepresented. A lectotype is designated for Augochlora iphigenia Holmberg, 1886. Oxystoglossa semiramis Schrottky, 1911,and Halictus brochidens Vachal, 1911, are new synonyms of A. iphigenia Holmberg. Odontochlora thebe Schrottky, 1909,is a new synonym of Odontochlora amphitrite Schrottky, 1909